A Bit Exagerrated Role of Complete Blood Count Parameters on the Prognosis of Idiopathic Sudden Sensorineural Hearing Loss - Senem Deveci Hande; Deveci Ildem; Toraman Murat; Aslan Dündar Tuğba; Erden Habeşoğlu Tülay; Habeşoğlu Mehmet; Karavuş Ahmet (Journal of Otolaryngology Advances, 2016)
Idiopathic sudden sensorineural hearing loss (ISSHL) is a commonly seen otorhinolaryngology emergency, and its etiology is still a mystery. In this retrospective clinical study, we aimed to investigate the possible relationship of inflammatory markers derived from CBC such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), Red cell distribution width-to-platelet ratio (RPR), lymphocyte-to-monocyte ratio (LMR), mean platelet volume (MPV) and platelet distribution width (PDW) in ISSHL . A total of 50 idiopathic sudden hearing loss patients were included in the study. They were grouped according to their hearing healing levels as recovered, partially recovered and unrecovered. Also 47 age- and sex- matched healthy individuals created the control group. Their complete blood count parameters of NLR, LMR, PLR, RPR, PDW and MPV were recorded. The results were statistically compared to bring out a significant difference between the groups. There was no significant demographic difference between the groups. The comparison of patient group with control group reveal a significant difference in the NLR, LMR and PDW values (p<0.05). The remaining values were not statistically significant. The analysis of these values according to the recovery level of the ISSHL, there was no statistical difference between the groups (p>0.05). We demonstrated for the first time that LMR value was significantly elevated in ISSHL patients. NLR, LMR, and PDW might be indicative for diagnosis of ISSHL. However, we believe that using these parameters for the screening of the prognosis is a clinically useless exercise.
Keywords: idiopathic sudden sensorineural hearing loss